FEATURES OF TEACHING A DISCIPLINE "MEDICAL AND BIOLOGICAL PHYSICS" FOR FOREIGN STUDENTS IN ENGLISH LANGUAGE IN HIHER MEDICAL EDUCATION - Gutsul, Oksana; Biriukova, Tetiana (Educological discourse, 2019)
The article deals with the peculiarities of the teaching of the discipline "Medical and Biological Physics" to foreign students in the English language of the highest state educational institution of Ukraine "Bukovinsky State Medical University". Expansion of international relations in science and the world is one of the main manifestations of Ukraine’s integration into the world of information space, impossible without a language that has long become international - the English language. A significant number of modern scholars actively study the features of methods of training foreign students, including in the direction of physics and mathematics. However, attention is not paid to the study of specific features of teaching these disciplines to foreign students. Problems of foreign students at the adaptation stage are related to the new requirements of Ukrainian higher education, with their status as a foreigner in Ukraine, with the features of age psychology, with their national-psychological peculiarities. The purpose of teaching physical and mathematical disciplines, in particular, medical and biological physics, of course, should be the close connection between a physical phenomenon or a process with its application in medicine for the purpose of diagnosis, treatment and prevention of diseases. To facilitate perception and understanding of physical phenomena or processes, it is expedient to use demonstration physical models, to perform laboratory work with the processing of measurement results and to formulate conclusions. Particularly important for foreign students is the availability of English-language textbooks that correspond to the curriculum of the discipline according to the number of academic hours covering topics from lectures and practical classes. Due to the constant increase in the number of foreign students studying in English, the necessary condition is to provide a well-prepared teaching and learning material that would cover the theoretical foundations and practical skills in discipline, in particular, the physical and mathematical direction, and ensure close communication with it, with future professional activities of students.